WAYS OF DEVELOPMENT OF BASIC PHYSICAL TRAINING OF MODERN YOUTH - Neus, D. V.; Shalamov, D. S. (Rehabilitation and Recreation, 2021)
Physical training is an important part of adolescent health. Encouraging children and adolescents to lead a healthy lifestyle is important as they grow. The lifestyle learned in childhood is more likely to remain in adulthood. The purpose of the study: to find out the ways of development of basic physical training of modern youth. This study used standard systematic review procedures that include transparent and principled methods for identifying, describing, evaluating, and comparing research on a specific issue. The review was innovative in that it aimed to answer not only the question of effectiveness, but also the question of the appropriateness of interventions in terms of whether they meet the necessary needs of young people. Young people suggested: create more bike paths, increase the availability of classes and provide more acceptable forms of physical activity (for example, not very structured and organized by adults). Although young people believe that they have enough information about the available facilities, some want more agreement on the desired levels of activity. Interventions that take into account the views of young people and therefore require careful evaluation include those aimed at: expanding the range of free activities through extracurricular clubs and community- based initiatives, providing community and school facilities for safe cycling, and improving school facilities for physical education. Providing such conditions gives young people the opportunity to choose types of physical activity and emphasizes the entertainment and social aspects of sports. Future initiatives to promote physical activity among young people need to take their views into account.